Copper-mediated cross-coupling reactions - Evano, Gwilherm; Blanchard, Nicolas (Wiley, 2014)
"Providing insight into the use of copper in cross-coupling reactions as a cost-efficient alternative to palladium, Copper-Mediated Cross Coupling Reactions provides a complete up-to-date collection of the available catalytic systems and processes. This essential reference covers a broad scope of copper-mediated reactions, their variations, key advances, improvements, and an array of applications that have revolutionized copper catalysis for any industry involving organic synthesis. The text discusses recently developed methods for conducting copper-mediated reactions with supported catalysts, which allow for recyclable and reusable systems"--